Strengthening Consumer Loyalty by Provider Communication Products In Industry 4.0 - Fithriani, Merry (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
In this study, the influence of perceived value on consumer loyalty and the impact of marketing mix communication on both will be investigated. This study also considers how perceived value mediates the influence of marketing mix communication on consumer loyalty. 125 By.U mobile card consumers in Bandung, West Java, received surveys from researchers using quantitative methods. The data were analyzed using SmartPLS 3.0 structural equation modeling. The positive impact of Marketing Mix Communication on consumer loyalty and perceived value is demonstrated in this study. Perceived value also impacts consumer loyalty. This study also provides evidence supporting the idea that the relationship between marketing mix communication and consumer loyalty is mediated by perceived value.